Graves’ disease and thyroiditis can be differentiated using only free thyroid hormone levels - Sümbül, Hilmi Erdem; Acıbucu, Fettah (The European Research Journal, 2020)
Objectives: As the treatment approaches of Graves’ disease and thyroiditis are different, differential diagnosis is important. In this study, we analyzed whether it is possible to perform a differential diagnosis for these two conditions by checking the increase ratio of free thyroid hormones. Methods: In total 156 patients were taken into this study of which 29 were thyroiditis (17 had subacute thyroiditis, 6 had post-partum and 6 had silent thyroiditis) and 127 were Graves patients. The age, free T3 (FT3), free T4 (FT4), thyroid stimulating hormone (TSH) levels, FT3 index (FT3/FT3 upper limit of normal (ULN)), FT4 index (FT4/FT4 ULN) and free thyroid hormone index (FTHI) (FT3 index/FT4 index) of all patients were determined. Results: A significant difference was found between the mean TSH, FT3 and FT3 index between Graves’ disease and thyroiditis (p = 0.036, p = 0.001 and p =0.001, respectively). When the groups were compared in terms of FTHI, the difference was found statistically significant (p = 0.001). FTHI was above 1 in all patients with Graves’ disease whereas it was found below 1 in all patients with thyroiditis. There were no statistically significant difference between the Graves’ disease and the thyroiditis in terms of age, FT4 and FT4 index (p = 0.748, p = 0.389 and p = 0.392, respectively). Conclusion: Based on these results, considering the increases in free thyroid hormone values we can say that it is possible to perform a differential diagnosis of Graves’ disease and thyroiditis, and that this may be used as a practical method to differentiate these two conditions.